The yeast EDC1 mRNA undergoes deadenylation-independent decapping stimulated by Not2p, Not4p, and Not5p - Muhlrad, Denise (2005)
A major mechanism of eukaryotic mRNA degradation initiates with deadenylation followed by decapping and 5′ to 3′ degradation. We demonstrate that the yeast EDC1 mRNA, which encodes a protein that enhances decapping, has unique properties and is both protected from deadenylation and undergoes deadenylation-independent decapping. The 3′ UTR of the EDC1 mRNA is sufficient for both protection from deadenylation and deadenylation-independent decapping and an extended poly(U) tract within the 3′ UTR is required. These observations highlight the diverse forms of decapping regulation and identify a feedback loop that can compensate for decreases in activity of the decapping enzyme. Surprisingly, the decapping of the EDC1 mRNA is slowed by the loss of Not2p, Not4p, and Not5p, which interact with the Ccr4p/Pop2p deadenylase complex. This indicates that the Not proteins can affect decapping, which suggests a possible link between the mRNA deadenylation and decapping machinery.